The leadwood tree (Combretum imberbe Wawra, family Combretaceae): Medicinal uses and ethnopharmacological properties - Maroyi, Alfred (Ethnobotany Research and Applications, 2025)
Background: Combretum imberbe Wawra is a medium to large semi-deciduous tree widely used in traditional medicine in tropical Africa. Aim: This study was aimed at reviewing the medicinal, phytochemical and pharmacological properties of C. imberbe. Methods: A search for available information on the medicinal, phytochemical and pharmacological properties of C. imberbe was conducted by searching the scientific databases such as Scopus®, PubMed®, Web of Science, ScienceDirect®, Google Scholar, SciELO and SpringerLink®, as well as pre-electronic literature sources such as book chapters, books and other scientific publications obtained from the university library. Results: This study showed that the bark, leaves, roots, root bark and stems of C. imberbe are used as charm, anthelmintic, hair relaxant, toothpaste and as ethnoveterinary medicine. Different parts of the species are also used as traditional medicine against bilharzia, erectile dysfunction, fever, malaria, gastro-intestinal problems, infertility in women, pregnancy troubles, menstrual problems, neuralgia, respiratory infections, sexually transmitted infections, skin problems and toothache. Chemical compounds identified from C. imberbe include amino acids, flavonoids, polyphenolics, tannins and triterpenoids. The crude extracts of C. imberbe and phytochemical compounds isolated from the species exhibited antibacterial, antimycobacterial, antifungal, anti-inflammatory, antioxidant, anti-proliferative, antischistosomal and cytotoxicity activities. Conclusion: To realize the full potential of C. imberbe as a valuable component of traditional pharmacopoeia in tropical Africa, future studies should focus on conducting detailed phytochemical, pharmacological and toxicological evaluations, in vivo and clinical research. Keywords: bush willow family, Combretaceae, Combretum imberbe, materia medica, traditional medicine